Epoxyeicosatrienoic acid analog attenuates angiotensin II hypertension and kidney injury - Hye Khan, Md. Abdul; Falck, John R.; Manthati, Vijaya L.; Campbell, William B.; Imig, John D. (Frontiers in Pharmacology, 2014)
Epoxyeicosatrienoic acids (EETs) contribute to blood pressure regulation leading to the concept that EETs can be therapeutically targeted for hypertension and the associated end-organ damage. In the present study, we investigated anti-hypertensive and kidney protective actions of an EET analog, EET-B in angiotensin II (ANG II)-induced hypertension. EET-B was administered in drinking water for 14 days (10mg/kg/d) and resulted in a decreased blood pressure elevation in ANG II hypertension. At the end of the two-week period, blood pressure was 30 mmHg lower in EET analog-treated ANG II hypertensive rats. The vasodilation of mesenteric resistance arteries to acetylcholine was impaired in ANG II hypertension; however, it was improved with EET-B treatment. Further, EET-B protected the kidney in ANG II hypertension as evidenced by a marked 90% decrease in albuminuria and 54% decrease in nephrinuria. Kidney histology demonstrated a decrease in renal tubular cast formation in EET analog-treated hypertensive rats. In ANG II hypertension, EET-B treatment markedly lowered renal inflammation. Urinary monocyte chemoattractant protein-1 excretion was decreased by 55% and kidney macrophage infiltration was reduced by 52% with EET-B treatment. Overall, our results demonstrate that EET-B has anti-hypertensive properties, improves vascular function, and decreases renal inflammation and injury in ANG II hypertension.